Effects of crystal habit modifiers on characterization parameters of tetrazene - Ryšavý, Jan; Matyáš, Robert (University of Pardubice, 2021)
This work has studied the effects of modifying agents on the behavior of industrially important primary explosive – tetrazene. Namely, of interest were the powder characteristics (particle size, bulk density and angle of repose) and sensitivities to external stimuli (friction, impact). The agents consisted of a wide group of materials when the following ten were selected: dextrin, sodium carboxymethylcellulose, gum arabic, sodium layrylsulfate, p-toluenesulfonic acid, polystyrenesulfonic acid, 1,6-diaminohexane, polyacrylamide, sunflower lecithin, and bone glue. No general correlation between the agent structure and the results were found, but some partial behavior patterns could be identified. The bulk density ranged from 0.2 g∙cm–3 at the low end for unmodified samples to 0.5 g∙cm–3 at the highest improvement. The angle of repose shifted from 60° for the unmodified form to 52° at best flowability (for the ball ammonium perchlorate as a reference value of 30°). The effect on the friction sensitivity is minuscule and all the samples had their F50 values within 3–7 N range. Three different groups separated for the impact-stimulus behavior – unaffected, sensitivity lowered to that of PETN or RDX, and erratic behavior. The particle size was generally in the 100 μm scale, but the crystal habit varied significantly.
Keywords: tetrazene; characterization; crystal modifiers; sensitivity; bulk density; flowability